Generation and analysis of mouse embryonic stem cells with knockout of the Mcph1 (microcephalin) gene - A. M. Yunusova; A. V. Smirnov; T. A. Shnaider; I. E. Pristyazhnuk; S. Y. Korableva; N. R. Battulin (Вавиловский журнал генетики и селекции)
Chromatin is not randomly distributed within the nucleus, but organized in a three-dimensional structure that plays a critical role in genome functions. Сohesin and condensins are conserved multi-subunit protein complexes that participate in mammalian genome organization by extruding chromatin loops. The fine temporal regulation of these complexes is facilitated by a number of other proteins, one of which is microcephalin (Mcph1). Mcph1 prevents condensin II from associating with chromatin through interphase. Loss of Mcph1 induces chromosome hypercondensation; it is not clear to what extent this reorganization aﬀects gene expression. In this study, we generated several mouse embryonic stem cell (mESC) lines with knockout of the Mcph1 gene and analyzed their gene expression profile. Gene Ontology analyses of diﬀerentially expressed genes (DEGs) after Mcph1 knockout revealed gene categories related to general metabolism and olfactory receptor function but not to cell cycle control previously described for Mcph1. We did not find a correlation between the DEGs and their frequency of lamina association. Thus, this evidence questions the hypothesis that Mcph1 knockout-mediated chromatin reorganization governs gene expression in mESCs. Among the negative eﬀects of Mcph1 knockout, we observed numerous chromosomal aberrations, including micronucleus formation and chromosome fusion. This confirms the role of Mcph1 in maintaining genome integrity described previously. In our opinion, dysfunction of Mcph1 may be a kind of “Rosetta stone” for deciphering the function of condensin II in the interphase nucleus. Thus, the cell lines with knocked-out Mcph1 can be used to further study the influence of chromatin structural proteins on gene expression.